Eye-Neck Integrated Ultrasound in Idiopathic Intracranial Hypertension and Cerebral Venous Sinus Thrombosis - Liu, Li; Xing, Yingqi; Chen, Ying; Ji, Xiaorui; Ge, Jiaojiao; Wang, Lijuan (Frontiers in Neurology, 2021)
Background: The clinical presentation of cerebral venous sinus thrombosis (CVST) overlaps with that of idiopathic intracranial hypertension (IIH), but no screening tool exists. We investigated the role of eye-neck integrated ultrasound in the diagnosis and differentiation of IIH and CVST. Methods: Twenty IIH patients, 30 CVST patients, and 40 healthy controls were retrospectively analyzed. The ultrasonographic optic nerve sheath diameter (ONSD) and hemodynamic characteristics of the internal jugular veins (IJVs) were recorded. The cerebrospinal fluid opening pressure was measured after ultrasonic examination. Results: The ONSD was significantly larger in IIH patients than in controls (4.71±0.41 vs. 3.93±0.24 mm, p<0.001). The ONSD cut-off for IIH diagnosis was 4.25 mm (AUC=0.978; 95% CI: 0.95-1.0, p<0.001, sensitivity: 90%, specificity: 93%). In the CVST group, 22 (73.3%) patients had elevated intracranial pressure (ICP); the mean ONSD was significantly higher in patients with increased ICP than in those without (4.43±0.33 vs. 3.95±0.17 mm, p<0.001). The mean blood flow volume (BFV) was significantly reduced in CVST patients (425.17±349.83 mL/min) compared to that in controls (680.37±233.03 mL/min, p<0.001) and IIH patients (617.67±282.96 ml/min, p=0.008). The optimal BFV cut-off for predicting CVST was 527.28 ml/min (AUC=0.804, 95% CI: 0.68-0.93, p<0.001, sensitivity: 80%, specificity: 78%). The velocity of the unilateral IJVs-J3 segment decreased or remained constant during deep inspiration (abnormal respiratory modulate blood flow test, ARMT) in 32.5% of controls, with no bilateral ARMT. The prevalence of bilateral ARMT was 25% in IIH patients (2=12.9, p=0.005) and 27% in CVST patients (2=17.6, p=0.001). Conclusion: Eye-neck integrated ultrasound is an easily available bedside technique to assess ICP and hemodynamic characteristics of IJVs. ONSD measurement can identify patients with increased ICP, and reduced IJV BFV may aid the differentiation of CVST and IIH.